APPLICATION OF CRITICAL THINKING TECHNIQUES IN THE CLASSROOM (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the crucial role of critical thinking techniques in enhancing the teaching and learning process in modern education. Critical thinking is recognized as one of the essential competencies of the 21st century, as it enables learners to go beyond memorization and engage in deeper levels of analysis, evaluation, and synthesis of knowledge. The article emphasizes that the systematic application of critical thinking techniques—such as questioning strategies, problem-solving tasks, debates, case studies, and collaborative learning—not only develops intellectual skills but also nurtures creativity, independent learning, and responsibility among students.Furthermore, the study highlights how teachers serve as facilitators in this process, guiding learners through constructive feedback, inquiry-based activities, and reflective practices. By integrating these techniques into classroom instruction, teachers can foster an active learning environment where students are encouraged to ask questions, challenge assumptions, and explore multiple perspectives. The paper also discusses the potential challenges educators may face in implementing these strategies, such as time constraints, curriculum limitations, and students’ lack of prior exposure to critical thinking tasks.